Comparison of bilateral cerebral and somatic tissue oxygenation with near-infrared spectroscopy in cyanotic and acyanotic pediatric patients receiving cardiac surgery - Candan, Tülay; Candan, Muhammet; Yıldız, Cenk Eray; Gümüştaş, Mehmet; Erentürk, Selim; Yalçınbaş, Yusuf Kenan (Termedia Publishing House, 2020)
Introduction: Compromise of tissue oxygenation during surgery is associated with increased mortality and morbidity in the postoperative period in patients with congenital cardiac disorders. It may be monitored with near-infrared spectroscopy (NIRS). We aimed to evaluate the tissue oxygenation and factors which may affect it by bilateral cerebral and somatic NIRS levels during cardiopulmonary bypass and to compare the NIRS values of cyanotic and acyanotic patient groups. Material and methods: Two groups of patients with cyanotic and acyanotic congenital heart diseases were included in the study. Each group consisted of 15 patients between 0 and 5 years of age. All data were collected following anesthesia induction (T1), the 10th (T2) and 30th min (T3) of cardiopulmonary bypass (CPB), every 30 min during CPB (T4, T5, T6) and 1 h after (TS). Bilateral and somatic NIRS, blood gases, mean arterial pressure, and temperatures were recorded. Results: Left and right somatic NIRS values in groups at all measurements did not differ significantly. Left and right cerebral NIRS values at T2 and T3 in cyanotic patients were significantly higher than in acyanotic patients. Mean arterial pressure and lactate levels at T1 and T3 measurements were responsible for left cerebral NIRS changes and mean arterial pressure on right cerebral NIRS values. Conclusions: Monitorization of tissue perfusion has critical importance during CPB of patients with congenital heart defects. Oxygenation may easily and reliably be measured with NIRS. Cerebral and somatic NIRS are more pronounced in cyanotic patients and cerebral NIRS is strongly associated with mean arterial pressure and circulating lactate levels.
Keywords: Near-Infrared Spectroscopy; Cerebral Oxygenation; Somatic Oxygenation; Cardiopulmonary Bypass; Congenital Cardiac Surgery